Young–Burgess classification: Inter-observer and inter-method agreement between pelvic radiograph and computed tomography in emergency polytrauma management. Issue 3 (May 2021) - Cheung, Jason; Wong, Cheuk Kei Kathy; Yang, Marc Li Chuan; Wong, Oi Fung; Cheung, Michelle; Lui, Chun Tat; Tsui, Kwok Leung
Background: While there are intrinsic differences in the pros and cons between plain radiographs and computer tomography, the role of pelvic radiographs in polytrauma management is diminishing as computer tomography scans are becoming more accessible. Previous studies found varying results in the inter-observer agreement in pelvic radiograph interpretations. Objectives: To evaluate inter-observer agreement of classifying pelvic fractures in major trauma patients by emergency physicians, and the inter-method agreement between plain radiographs and computer tomography scans. Methods: Three hundred sixty-nine patients with pelvic trauma were recruited from the trauma registries of four designated trauma centres in Hong Kong, each having one set of anteroposterior pelvic radiographs and pelvic computer tomography scans. Pelvic radiographs were classified by two emergency physicians using Young–Burgess classification, and pelvic computer tomography scans classified by an experienced radiologist. Disagreed pelvic radiographs were evaluated by a senior emergency physician to make a final decision before comparing with computer tomography scans. Cohen's kappa was used to measure the inter-observer and the inter-method agreements, in the groups 'mechanism of injury', 'stable versus unstable fractures' and 'complete classification'. Results: Inter-observer agreements of plain radiograph classification for 'mechanism of injury', 'stable versus unstable fractures' and 'complete classification' were moderate to substantial (κ = 0.72, 0.60 and 0.55, respectively). Inter-method agreement for the three groups between plain radiographs and computer tomography were fair to moderate (κ = 0.42, 0.59 and 0.38, respectively). Conclusion: The inter-method agreement between plain pelvic radiographs and computer tomography scans was fair in classifying pelvic fractures, and moderate in detection of unstable pelvic fractures. If the patient is haemodynamically unstable or when computer tomography is unavailable, it is reasonable to obtain plain radiographs to screen for unstable pelvic fractures to expedite early intervention. A review in the education approach and material of Young–Burgess classification may improve inter-observer agreement.